The Early Growth and Development of 10 Genotypes Gajah Ginger as Intercrops System in Jatropha curcas Plantation - Prasetyo, Yudi; Zainudin, Agus; Muhidin, Muhidin (Journal of Tropical Crop Science and Technology, 2020)
Ginger (Zingiber officinale Rosc.) is one of the medicinal plants and can be processed into products such as essential oils and starches. Ginger was planted under a tree because it has a good sunlight tolerant plant. Ginger can grow and develop normally, even in low light intensity. Indonesia has a lot of land with shade conditions and potential for ginger production. It can be supported to increase national ginger production. This study aims to assess the growth and development of ginger in Gajah variety, with several genotypes, that are cultivated as intercropping at Jatropha curcas. The study was conducted in Jatropha plantation at 2.144 dap age, which is located at Desa Kedungpenggaron, Kec. Kejayaan, Pasuruan city (117 m above sea level, with coordinates 7 ° 46'18.6 "112 ° 50'25.2"). The study began on October 2017 to March 2018. The study used Gajah variety, with 10 genotypes, consist of Banyuwangi, Sidoarjo, Malang, Bojonegoro, Jombang, Bandung, Purwakarta, Banten, Lampung, Jambi, which were arranged in a Randomized Block Design. The results showed that ginger's growth and development at 14 to 105 dap was not significantly different in all parameters. Based on cluster analysis for 14 quantitative variables, showed that two grouped, specifically 9 genotypes and 1 Lampung's genotype with 31.71% similarity. The similarity of Ginger Gajah, approved by the Banyuwangi and Jombang genotypes, which reached 86.26%.